The Code: Containing All the Statutes of the State of Iowa 76-77 (1873) - (:unkn) unknown (My University, 1873)
§ 453: Cities and towns shall have the authority to prevent injury and annoyances from transportation and keeping of gunpowder and other combustibles, and licensing of powder magazines.
Keywords: GUNPOWDER - TRANSPORTATION